Salidroside ameliorates liver metabonomics in relation to modified gut-liver FXR signaling in furan-induced mice. (June 2020) - Yuan, Yuan; Wu, Xuan; Hong, Yilin; Zhang, Xu; Wang, Ziyue; Yan, Haiyang
Abstract: The study aimed to investigate the ameliorative effect of salidroside (SAL) on the crosstalk among liver metabonomics, gut barrier function and bile acids in furan-induced mice. Forty male mice were randomly divided into the following five groups: CON, FUR 8 (8 mg/kg/day furan), SAL 10 (8 mg/kg/day furan+10 mg/kg/day SAL), SAL 20 (8 mg/kg/day furan+20 mg/kg/day SAL), and SAL 40 (8 mg/kg/day+40 mg/kg/day SAL). Mice were administered with furan for 30 days and SAL was administered for 15 days from day 16. Principal components analysis (PCA) and heatmap were employed to probe metabonomics profile alterations in liver tissues and select thirty-eight potential biomarkers. Pathway analysis revealed primary bile acids were largely changed in the biosynthesis pathway. Moreover, SAL regulated the activation of farnesoid X receptor (FXR), downregulating hepatic heterodimer partner (SHP), upregulating cholesterol 7a-hydroxylase (CYP7A1) as well as decreasing the expression of portal fibroblast growth factor 15 (FGF15), compared to the furan-treated group. Importantly, SAL dramatically increased the level of tight junction proteins, as immunohistochemistry results show. In conclusion, the ameliorative effects of SAL on liver damage induced by furan might be due to altered gut barrier function, while FXR signaling acted a significant role in the function of SAL. Graphical abstract: SAL play an ameliorative role to affect liver metabonomics in relation to modified gut-liver FXR signaling in furan-induced mice. Image 1 Highlights: Thirty-eight metabolites were identified by LC-MS system in FUR 8 group. As the dose increasing, SAL altered at least 9 metabolites compared to FUR 8 group. SAL changed the primary bile acids pathway compared to FUR 8 group. SAL improved liver injury caused by furan by affecting gut barrier function.